Project Management Learning: A Comparative Study between Engineering Students' Experiences in South Africa and the United Kingdom. Issue 4 (August 2015) - Ojiako, Udechukwu; Chipulu, Max; Marshall, Alasdair; Ashleigh, Melanie J.; Williams, Terry
This study explores how engineering students studying project management perceive their learning experiences. To facilitate an understanding of the constituent components of engineering students' experiences and to understand how these experiences influence preferred learning styles, a comparative study of university students studying engineering in South Africa and the United Kingdom is conducted. The study finds no significant demographic differences in learning experiences across the two student cohorts. However, the South African cohort reports higher levels of overall experiences. They also report higher usage of online learning materials but lower levels of blended learning and individual critical evaluation skills experiences.